2018
DOI: 10.14419/ijet.v7i4.13.21341
|View full text |Cite
|
Sign up to set email alerts
|

A case study of LEAN application for shortest lead time in composite repair shop

Abstract: Lean tools and applications have been adopted globally by many companies and industries such as automotive, aerospace, healthcare, pharmaceutical, shipbuilding, public services, project management and several others. The most basic of lean tools can be distinguished by the following: Value Stream Mapping (VSM), 5S and Kaizen, and many have agreed that these are the best selections in the initial approach of lean system and these techniques are part of the Y Management System (YMS) initiatives. This research is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The main concepts of the Lean philosophy are applied in projects of both companies, aiming to reduce waste, obtain better results and deliver value to their clients. Authors Hussain (2019) and Ishak et al (2018) reported similar objectives and proved the benefits of applying lean tools (5S, VSM) and principles to save energy and damage to the environment or to maximise profits and minimise costs, respectively.…”
Section: Research Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The main concepts of the Lean philosophy are applied in projects of both companies, aiming to reduce waste, obtain better results and deliver value to their clients. Authors Hussain (2019) and Ishak et al (2018) reported similar objectives and proved the benefits of applying lean tools (5S, VSM) and principles to save energy and damage to the environment or to maximise profits and minimise costs, respectively.…”
Section: Research Resultsmentioning
confidence: 92%
“…The numerous benefits of implementing Lean, which nowadays represents the Toyota Production System (TPS) approach, have become globally acknowledged. Currently, standards and approaches are vastly applied beyond the automotive context (Ishak et al, 2018), thus, impelling the creation of innovative approaches within organisations (Singh et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations